Memória e migração presentes em narrativas orais de migrantes nordestinos na Amazônia paraense - PIMENTEL, Flávio Reginaldo (Universidade Federal do Pará, 2014)
This study analyzes oral narratives and life stories of migrants who have established residence in northeastern Pará Amazon called, more precisely in the region called Bragantina in the municipality of Igarapé Açu. For this purpose, we use categories like Memory and Migration, as well as its relationship with Culture and Popular Culture and how this fits in Oral Literature and Popular Literature of the region. Because we believe that orality has greatly contributed to the solidification of Popular Culture and its diversity, but this is not considered. It is noteworthy that this work wants to be a contribution to the understanding of this enormous cultural diversity of the region, from the migration occurred. Collect stories of migrants who live in the municipality of Igarapé Açu, in trying to understand all this and effervescent cultural range, which is typical of regions where migration is strong. The memory has also contributed significantly to the studies related to orality and its cultural features resulting from it.